Pengoptimalan Biaya Distribusi Bahan Material Keramik Menggunakan Metode Least Cost - Ziaulhaq, Muhammad Haikal; Affandi, Aisyah; Aritonang, Sovian (Equiva Journal, 2024)
PT. Indah Bangunan is a ceramic distributor company located in Palu City. This study aims to determine the optimal transportation costs for ceramic distribution to improve operational efficiency. The steps taken include developing a transportation model based on actual data, determining an initial solution using the Least Cost method, and refining the solution with the Stepping Stone method to achieve optimal results. Based on the analysis, the initial solution obtained using the Least Cost method produced the same results as the optimal solution obtained through the Stepping Stone method, demonstrating that this approach is effective in minimizing transportation costs.